Symptom heterogeneity in students with mild to severe depression symptomatology and their differential symptom-specific changes during an internet-based, guided cognitive behavioural therapy intervention - Lynn Boschloo; Jasmijn Wijnands; Nadia Garnefski; Vivian Kraaij; Petra Hurks; Danielle Remmerswaal; Reinout W. Wiers; Sascha Struijs; Elske Salemink (Internet Interventions)
Background: Students often report depression and stress symptomatology but may differ in their symptoms and their symptom-specific changes during interventions. This study adopted a symptom-specific approach and examined 1) individual symptoms in students experiencing mild to severe depression symptomatology and 2) changes in individual symptoms during a guided, internet-based intervention. We zoomed in on how these (changes in) symptoms were related to each other and to (changes in) overall quality of life. Methods: This study included 1816 students with mild to severe baseline depression symptomatology, of which 412 activated their account for an eight-week, guided, internet-based Cognitive Behavioural Therapy intervention (Moodpep) and completed the post-treatment assessment. Depression symptomatology was assessed with the Patient Health Questionnaire, stress symptomatology with the Perceived Stress Scale and overall quality of life with a single item from the Mental Health Quality of Life questionnaire. Network estimations were conducted to examine the interrelations of (changes in) symptoms. Results: Mean scores of baseline symptoms differed substantially, and network estimations showed multiple positive connections across symptoms and negative connections of symptoms with overall quality of life. During the intervention, all symptoms reduced significantly, although with differential magnitude, and network estimations showed that changes in symptoms were differentially related to other changes in symptoms and changes in overall quality of life. Conclusions: Our findings highlight the importance of considering individual symptoms and their interrelations as a more complete and nuanced measure for 1) the heterogeneity of baseline symptomatology and 2) the heterogeneity of changes in symptomatology during an intervention.